A Strategy to Achieve Well-Dispersed Hollow Nitrogen-Doped Carbon Microspheres with Trace Iron for Highly Efficient Oxygen Reduction Reaction in Al-Air Batteries. Issue 16 (7th December 2018) - Li, Jingsha; Fu, Liang; Luan, Jingyi; Xie, Hualin; Cheng, Fangyi; Tang, Yougen; Wang, Haiyan
Abstract : Well-dispersed hollow nitrogen-doped carbon microspheres with trace amount of iron have been fabricated by a vapor-pressure driven polymerization of pyrrole on polystyrene sphere templates, followed by a pyrolysis. Owing to the special processing technique, the vapor pressure driven pyrrole polymerization could be well controlled and thus monodispersed hollow microspheres could be well formed. The resultant optimized sample exhibits excellent electrocatalytic activity toward oxygen reduction reactions (ORR) with a half-wave potential (E1/2 ) of 0.832 V (vs. RHE) and a limiting-current density (JL ) of 5.92 mA cm −2, which is better than the commercial 20 wt% Pt/C. This catalyst also shows much higher discharge voltages in practical Al-air batteries than Pt/C (1.56 V Vs 1.45 V) at a discharging current density of 40 mA cm −2 . The enhanced catalytic activity mainly originates from the high content of pyridinic and graphitic N in-situ doping.